Performance progression in Brazilian middle-distance runners from early training to peak performance: a pilot study - Andrigo Zaar; Victor Machado Reis; Diogo Roberto Oliveira; António José Silva (Universidade Federal de Santa Catarina, 2013)
The aim of this study was to evaluate performance progression in Brazilian middle-distance runners based on the progression of their sports results from early training to peak performance. The sample consisted of the 10 best performance times (800 m and 1500 m) achieved by male runners aged 15 to 19 years in national rankings between 2001 and 2010. The 800-m performance times estimated with the models were 119.14±1.79 s at 15 years of age; 114.36±1.07 s at 16 years; 113.25±1.81 s at 17 years; 110.71±1.60 s at 18 years, and 109.73±1.17 s at 19 years. The prediction of 1500-m performance was 253.89±4.84 s at 15 years of age; 243.40±1.67 s at 16 years; 238.53±1.55 s at 17 years; 232.49±1.59 s at 18 years, and 230.48±2.28 s at 19 years. It is concluded that Brazilian male middle-distance runners achieve their best performance at 22.69±0.42 years of age in the 800-m event and at 22.29±0.34 years in the 1500-m event. These values are within the lower limit described in the literature as optimal age.